Balancing Marketing and Sharia Compliance: A Study of Da'wah Management Models at Halal Centers in UIN Sunan Kalijaga Yogyakarta and UIN Sunan Ampel Surabaya - Nurmadiansyah, M. Toriq; MZ, Ahmad Murtaza; Syahputra, Satria Tenun (Prodi Manajemen Dakwah STAIN Mandailing Natal, 2024)
This study investigates the management models of halal centers at UIN Sunan Kalijaga Yogyakarta and UIN Sunan Ampel Surabaya, focusing on balancing marketing strategies and sharia compliance. Using a qualitative methodology with a phenomenological approach, the research explores the perspectives of ten halal center managers through observations and semi-structured interviews. Thematic analysis reveals a multi-dimensional understanding of halal, extending beyond consumables to include behaviors and societal implications. Both institutions emphasize product excellence and community safety, though their approaches differ. Key findings highlight the importance of integrating religious, regulatory, and market-based perspectives in halal certification, enhancing consumer trust and business credibility. Challenges include divergent regulations between BPJPH and the MUI fatwa commission and the lack of an accessible online registration system. Future research should focus on harmonizing regulatory frameworks and expanding certification processes to other industries. This study underscores the pivotal role of Halal Centers in promoting halal literacy and supporting government initiatives, thereby fostering a robust halal industry in Indonesia.